INTEGRATED LIVESTOCK ADOPTION OF INNOVATION CASE STUDY: ARGOSARI AND ARGOREJO VILLAGE, SEDAYU DISTRICTS, BANTUL DISTRICT, D.I YOGYAKARTA PROVINCE - Supriadi Supriadi; Ali Agus; Muhadjir Darwin; Rijanta Rijanta; Ambar Pertiwiningrum (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
ABSTRACT Integrated farm is a model for the management of local resources’ potential by integrating livestock and crops into eco-friendly farming (zero waste). It can be the answer for the country’s basic needs of food that is still dependent on imports. Most of the habitants of Argorejo and Argosari village work as farmers and ranchers. Although the formal education of rural people is still low due to low income, the average member of activities to get information, knowledge and management skills in agribusiness sectors to understand the practical, economical, and effective ways in business development. It facilitates adoption of innovation and the process of information absorption. Adoption of innovation is a process of mental or behavioral changes in the form of knowledge (cognitive), attitudes (affective), and skills (psychomotor) since one recognizes the innovation until one decides to adopt it after receiving it. This is qualitative research, with research material in the form of members of agribusiness activities in the intervention program called Mandiri Bersama Mandiri. The method used is descriptive analysis. The data is collected by interview, observation, and records related to the activities of the group. The result of Classification Analysis with Adopter type shows that 7 of the 8 groups in the facilitation of innovation adoption of integrated farms have: 6.7% to 14.3% innovator; 8.3% to 18.2% early adopter; and the rest is 71.4% to 77.8% early majority. One group has no innovator and up to 50% early adopter. The innovators of Mandiri Bersama Mandiri program include the most influential people that have important positions, such as group leaders, village officials, or persons who have knowledge. It indicates that the potential success of the intervention program is located on the adopter type that exists in each member, absorption of new innovations adoption, and succeed in the community empowerment program.